Small angle X-ray scattering study of surface modified tin oxide nanoparticles prepared by sol-gel route - Kawaguti, C. A.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Craievich, A. F. (Springer, 2006)
The surface properties of SnO2 nanoparticles were modified by grafting ionic (Tiron (R). (OH)(2)C6H2(SO3Na)(2)(H2O)-H-.) or non-ionic (Catechol (R). C6H4-1,2-(OH)(2)) capping Molecules during aqueous sol-gel processing to improve the redispersibility of powdered xerogel. The effect of the amount of grafted organic molecules on the redispersibility of powders in aqueous solution at several basic pH values was Studied. The nanostructural features of the colloidal suspensions were analyzed by small angle X-ray scattering (SAXS) measurements. Irrespective of the nature and amount of grafted molecules, complete redispersion was obtained in aqueous solution at pH = 13. The redispersion at pH = 11 results in a mixture of dispersed primary particles and aggregates. The proportion of well dispersed nanoparticles and aggregates (and their average size) can be tuned by the quantity of grafted ionic molecules.
Keywords: nanoparticles; surface modification; SAXS